(untitled) (MAUSAM, 1988)
A scheme for the estimation of heavy convective rainfall over India during the monsoon season using 3-hourly INSAT-1B satellite data has been presented in this paper. The scheme uses ’life history’ approach, taking into account the convective cloud structure, cloud growth in space & time and the prevailing environmental conditions. The role of mesoscale convective complex, overshooting tops and cloud mergers in producing heavy rains is discussed. The scheme is applied to two very heavy rainfall events of August 1986 and August 1987 and some important aspects of the rainfall estimation have been discussed. For an independent data set, the percentage deviations of the rainfall estimates from actual lie between + 111% and -43 %, and 85% of the estimates lie within an error of +-5%. The scheme provides rainfall estimates on a near real-time basis and its accuracy is expected to Improve with the experience gamed In future.